Structural representation of additively manufactured 316L austenitic stainless steel. (July 2019) - Bronkhorst, C.A.; Mayeur, J.R.; Livescu, V.; Pokharel, R.; Brown, D.W.; Gray, G.T.
Abstract: Three 316L stainless steel materials are studied and reported upon; wrought, as-built additively manufactured (AM), and heat-treated AM material. The AM material was produced from the laser engineered net shaping (LENS) process. Macroscopic uniaxial compression stress-strain curves were obtained for all three materials. The curves were similar for the wrought and heat-treated AM materials but the as-built AM material demonstrated approximately 1.7 times greater flow stress at any given level of strain than the other two materials. Electron-backscatter diffraction analysis of the materials also showed that the microstructures of the three materials differed; with complex grain morphology for the as-built AM material. The mean grain size of each of the three materials also differed. The initial dislocation density was also measured with neutron diffraction and line-profile analysis for both wrought and as-built AM materials with the density in the AM material approximately 2.5 times greater. A single crystal model was proposed to represent the essential features of the three FCC materials accounting for dislocation interactions and representation of grain size via a simple Hall-Petch type term. The strength of this term is evaluated through independent experimental results on traditionally manufactured materials. The model was applied to each of the three materials by simulation of the uniaxial compression experiments by direct numerical simulation of electron-backscatter diffraction images. This allowed for representation of the size of each grain in the simulations. The results suggest that the difference in initial dislocation density of the three materials is the primary factor causing the difference in stress-strain response. Although the differences in grain size contribute to a higher stress for the as-built AM material, the effect is small. Other factors such as internal stress and grain morphology could play a role in mechanical behavior difference and these two factors are also discussed.